Truth Telling Activity: A Practice beyond the Norms (Global Journal of Management and Business Research, 2014)
The focus of this study is the ethical conduct of Brazilian accountants, based on the Foucault (2001b) approach concerning the practice of Parrhesia. It is aimed to find out how characteristics of truth-telling activities can be framed as perceived by Brazilian accountants according to their beliefs and identify differences between these beliefs and how they actually practice in their profession. The motivation for using this approach was the fact that the existence of a professional ethical code hasn't proven itself enough to curb moral deviations in professional conduct. This is an explor-atory and descriptive study with a quantitative approach. A survey was made through a structured questionnaire and featured a final sample composed of 5,087 respondents. Data were treated by descriptive analysis, Exploratory Factor Analysis (EFA) and Technical Analysis of Paired Data.
Keywords: parrhesia #x2013; professional ethics #x2013; accountants #x2013; brazil